Peran Guru Profesional Sebagai Fasilitator Dalam Kegiatan Pembelajaran di Sekolah Dasar - Nabilla Sapitri; Santi Sahtun Sahwal; Dina Satifah; Najwa Takziyah (Institut Pendidikan Indonesia, 2023)
In the learning process, the teacher is a component that forms the human element, and based on the development of the new curriculum, the teacher is needed as a facilitator. Teachers are expected to act as mentors and be able to find and use facilities that meet their learning needs. There are five indicators of the teacher's role as a facilitator. The first provides all learning tools; the second provides learning facilities; the third acts as a partner; the fourth carries out the duties and functions of a teacher; and the fifth provides students without acting arbitrarily. Overall, the teacher tries to act as a facilitator, even though it has not shown maximum results. The purpose of this article is to clarify the role of the teacher as a facilitator in teaching and learning activities.